G577(P) Targeted neonatal echocardiography. (25th October 2020) - Burman, A; Khan, S; Khushu, A; Kelsall, W
Abstract : Introduction: The incidence of congenital heart disease (CHD) varies between 6/1000 live births for moderate/severe CHD to 75/1000 for trivial lesions e.g. small muscular ventricular septal defects.¹ There are no guidelines for which neonates undergoing non-cardiac surgery require a pre-operative echocardiogram (POE). Paediatric anaesthetists and surgeons often request for stable babies to have a POE before surgery. In this unit, paediatricians with expertise in cardiology (PECs) perform these scans, often being approached out of hours. Aims: To review the cardiovascular status of babies undergoing surgery before 28 days corrected age and determine if the clinical examinations correlated with POE. Methods: Patients undergoing non-cardiac surgery less than 1 month corrected age between April 2015 – 2018 were identified using the Trust Theatreman system. Data was subsequently collected from the Badgernet and Epic systems. Results: We reviewed 270 surgical events in 235 patients. 173 (74%) had a normal clinical examination and 125 (53%) had POE. Of the 173 babies with normal examinations 71 (41%) had a POE, which was abnormal in only 6 (3%). In the 62 babies with an abnormal examination, a POE was performed in 54 (87%) babies with 14 (26%) having more significant CHD. Of the 125 POE only 16% were abnormal. Conclusions: There was a good correlation between normal examination and normal POE. An abnormal examination was more frequently associated with an abnormal POE. In developing local guidelines, we would hope to agree that a POE is not required in patients with normal examinations. Such patients could safely have echocardiography screening post-operatively.